2004
DOI: 10.1158/0008-5472.can-04-0446
|View full text |Cite
|
Sign up to set email alerts
|

17β-Hydroxysteroid Dehydrogenase Type 1 Is an Independent Prognostic Marker in Breast Cancer

Abstract: Estrogens have an important role in the development and progression of breast cancer. 17␤-Hydroxysteroid dehydrogenase type 1 (17HSD1), type 2 (17HSD2), and type 5 (17HSD5) are associated with sex steroid metabolism in normal and cancerous breast tissue. The mRNA expressions of the 17HSD1, 17HSD2, and 17HSD5 enzymes were analyzed in 794 breast carcinoma specimens by using tissue microarrays and normal histologic sections. The results were correlated with the estrogen receptor ␣ (ER-␣) and ␤ (ER-␤), progesteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 37 publications
4
97
2
Order By: Relevance
“…In humans, the closely related 17β-hydroxysteroid dehydrogenase is responsible for sex steroid metabolism (conversion of active estradiol to the less potent estrone) in normal and tumor tissues. It has been found to be up-regulated in breast tumors (Oduwole et al 2004) and, conversely, has also been found to be reduced in colonic tumors (English et al 1999). The apparent increase in expression of 3β-hydroxysteroid dehydrogenase in HC from female fish may indicate estrogen exposure and subsequent estrogen inactivation, and may be an important mechanism in the pathogenesis of HC.…”
Section: Discussionmentioning
confidence: 95%
“…In humans, the closely related 17β-hydroxysteroid dehydrogenase is responsible for sex steroid metabolism (conversion of active estradiol to the less potent estrone) in normal and tumor tissues. It has been found to be up-regulated in breast tumors (Oduwole et al 2004) and, conversely, has also been found to be reduced in colonic tumors (English et al 1999). The apparent increase in expression of 3β-hydroxysteroid dehydrogenase in HC from female fish may indicate estrogen exposure and subsequent estrogen inactivation, and may be an important mechanism in the pathogenesis of HC.…”
Section: Discussionmentioning
confidence: 95%
“…There is only one study that has investigated the prognostic importance of 17HSD5 in breast cancer. The authors found that patients with high 17HSD5 expression in the tumor had a worse prognosis than the group with low or no expression (8). The importance of 17HSD5 in breast cancer needs to be further clarified.…”
Section: Introductionmentioning
confidence: 98%
“…The SDR family consists of oxidoreductases that participate in the metabolism of steroids, prostaglandins, and retinoids (4). In breast tissue, several 17HSD family members have been reported to be present, such as 17HSD1, 17HSD2, 17HSD5, and 17HSD12 (5)(6)(7)(8)(9)(10)(11). Although 17HSD1 and 17HSD2 are the main 17HSD enzymes involved in breast cancer investigated this far (7,8,10,11), it is possible that other hormone-regulating 17HSD enzymes may have a significant role in hormone-dependent tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Thin-layer chromatography (TLC) was performed on 0. 25 C respectively. Duplication of NMR signals was generally recorded for THP derivatives.…”
Section: Generalmentioning
confidence: 98%
“…Furthermore, a study revealed that the reductive activity (E 1 into E 2 ) is higher in malignant breast tumours whereas the oxidative pathway (E 2 into E 1 ) is dominant in normal breast cell [22]. 17b-HSD1 mRNA has been detected in malignant breast tumours by in situ hybridization, immunohistochemistry and reverse transcription-PCR [23][24][25]. It was also demonstrated that 17b-HSD1 plays a role in the local biosynthesis of estrogen in the breast, especially in postmenopausal women, after the ovaries have ceased to produce estrogen [26,27].…”
Section: Introductionmentioning
confidence: 99%